The Impact of Age and Parity in the Incident of Premature Rupture Membranes (PRM) - Tinuk Esti Handayani (Journal of Global Pharma Technology, 2020)
Introduction: One of the most prominent problems due to pregnancy complications is the incidence of PRM. Premature rupture of membranes(PRM) is a complication in pregnancy and childbirth that plays a role in increasing meternal-perinatal morbidity and mortality which can be caused by infection. The purpose of this study was to determine the effect of age and parity on the incidence of PRM PRM at Widodo Ngawi Hospital. Methods: Case control analytical observation research design. The sample of cases of maternal PRM with a sample size of 30 respondents. The sample of maternal control was 30 respondents. Samples were taken using simple random sampling technique. The independent variables are age and parity, and the dependent variable is PRM. Data collection used a secondary data type checklist. Data analysis used Logistic Regression Test with a significant level of 0.05. Results: The results showed that most of the mothers aged 35 years (79.3%) and p value = 0.004. The OR value of the age variable is 7,020, the conclusion is that age has a 7 times greater risk of causing PRM. Multigravida parity (72.2%) and p value = 0.010. The OR value of the parity variable is 6.481, it can be concluded that parity has a 6 times greater risk of causing PRM. p-value